Challenges and strategies in the translation of proper names - Omarova, A.S.; Raissova, A.B.; Kozhanova, G.A. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
Proper names (PNs) pose significant challenges in translation due to their cultural, historical, and linguistic significance. This study explores strategies for translating proper names across different languages, focusing on empirical data and theoretical models of research. The methodology involves a structured review of academic literature and case studies from Kazakh, Russian, English, and Chinese texts in both literary and formal genres. Our analysis is based on the translation strategy framework proposed by Newmark and extended by Fernandes, including transliteration, semantic translation, adaptation, and substitution. Findings show that proper name translation is highly context-sensitive: while legal and academic texts require standardization and transliteration, literary texts allow greater flexibility through adaptation and localization. Particular attention is given to Kazakh toponyms and anthroponyms, where inconsistencies in rendering affect both meaning and international comprehensibility. This study concludes that translating proper names requires balancing source-language fidelity with target-language readability and cultural relevance. Translators should apply context-aware strategies and align with national transliteration standards and international publication norms. The study concludes that proper name translation depends heavily on textual function, audience expectations, and the cultural load of the name itself.